Smart, Safe, and Strategic: Transforming HR Data into Actionable Insights Without Compromising Security - Singh, Kuwarpreet (The Eastasouth Journal of Information System and Computer Science, 2025)
In today’s digital age, healthcare organizations are starting to use Human Resource (HR) data to make informed workforce decisions, enhance staffing, promote employee well-being, and navigate the ever-evolving regulatory landscape. This shift is largely due to well-built analytics tools found in platforms like Workday, which provide HR leaders with real-time insights into key metrics such as turnover rates, performance trends, and skills gaps. However, with all these benefits come serious risks. HR data in healthcare often includes very private information like health records, salaries, and personal details. If this information falls into the wrong hands, it can cause legal problems, damage the organization’s reputation, and hurt employees. Because of this, it's not enough to just use data well—it must also be protected at every stage. This paper explores how healthcare institutions can effectively and safely transform HR data into actionable insights through advanced analytics, all while prioritizing data privacy and compliance. It examines modern encryption techniques, privacy-preserving machine learning, and data governance frameworks that empower HR teams to achieve better outcomes securely. By reviewing case studies, peer-reviewed research, and industry best practices, this paper sheds light on the challenges, solutions, and emerging trends that will define the future of secure, data-driven HR ecosystems in healthcare.